POLITIK HUKUM PENGATURAN ALAT PEMBATAS KECEPATAN DI KOTA PEKANBARU - Ester Nataliana; Dessy Artina; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
A speed limiting device, or in layman’s term, a speed bump, and commonly known as polisi tidur (lit. sleeping policeman) in Indonesia, is a traffic engineering tool that functions to control the speed of vehicles traversing on a road, particularly in residential areas to protect road users. The installation of a speed limiting device that is not in accordance with the existing standard safety procedure or regulation may cause discomfort to vehicle users passing over it or even result in danger or other disruptions.The purpose of this research is to conduct an in-depth study into the legal politics governing the regulation of speed limiting devices in Indonesia and to determine the ideal regulatory arrangements for speed limiting devices in the city of Pekanbaru. The research focuses on establishing evidence that there is no regulation that authorizes Pekanbaru citizens to make or install speed limiting devices at their own discretion.The research was conducted using an empirical judicial approach, which is a type of field research that examines the existing legal policies and observes what happens in its actual implementation in the society. The research data was gathered using 2 (two) data collection techniques, interviews and library research, and analyzed using a qualitative approach that produces descriptive data containing discussions or explanations on the features of the respondents based on their writing, verbal statements or real behavior. Based on the discussions, conclusion was drawn with deductive reasoning, which is a top-down logical approach of drawing conclusion starting from the general to the specific, whereby the researcher arrives at a conclusion by observing real variables and inferring specific information from the observation.The findings of this study suggest the fact that legal politics is manifested in the revision or amendments of legislation. In this case, it can be interpreted that the ebb and flow, or the continuous revision of laws governing speed limiting devices indicates the involvement of legal politics in regulating speed limiting devices in Indonesia, which leads to the change in the format or form of the regulation pertaining to speed limiting devices in Indonesia, particularly in Pekanbaru. To deal with the problem of speed limiting devices in Pekanbaru, it is recommended that a local regulation called the Mayor Regulation of Pekanbaru City be established as an ideal regulatory framework for speed limiting devices in Pekanbaru.Keywords : Legal Politics - Ideal Regulatory Arrangements - Speed Limiting Device